1999
DOI: 10.1051/forest:19990602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water stress conditioning on the water relations, root growth capacity, and the nitrogen and non-structural carbohydrate concentration of Pinus halepensis Mill. (Aleppo pine) seedlings

Abstract: -One-year-old Pinus halepensis seedlings were subjected to four water stress conditioning treatments (control,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
1
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 23 publications
2
39
1
10
Order By: Relevance
“…An osmotic adjustment potential as a response to water stress, that varies from provenance to provenance, is of the same type as that observed in 2-year-old Aleppo pine seedlings from Italian provenances [35]. Conversely, a study performed on only one provenance of Aleppo pine at the beginning of autumn has shown that drought did not induce any osmotic adjustment in 1-year old plants [38].…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…An osmotic adjustment potential as a response to water stress, that varies from provenance to provenance, is of the same type as that observed in 2-year-old Aleppo pine seedlings from Italian provenances [35]. Conversely, a study performed on only one provenance of Aleppo pine at the beginning of autumn has shown that drought did not induce any osmotic adjustment in 1-year old plants [38].…”
mentioning
confidence: 91%
“…This difference may be due to the fact that we did not re-hydrate our samples or to the fact that the seedlings we examined were younger. Conversely, Villar-Salvador et al [38] did not observe any WD 0 variations in Aleppo pines subjected to water stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, species may have different responses to N fertilization. For instance, Ypsat and Y p tlp in P. halepensis and P. pinea have small seasonal variations or little changes in response to drought (Villar-Salvador et al, 1999;Villar-Salvador et al, 2000). Kleiner et al (1992) found no differences in Ypsat and Yptlp in two oak species in well-watered plants grown under contrasted fertilization.…”
Section: Nitrogen Fertilization and Stress Resistance 415mentioning
confidence: 99%
“…Most North American nurseries reduce irrigation or fertilisation in late summer and fall as a part of this conditioning process [34,66]. Nevertheless, these latter treatments have not always been effective in inducing plant dormancy in Pinus halepensis seedlings [56,63]. This species shows osmotic adjustment as a response to water stress, although the response varies between the provenances [10].…”
Section: Introductionmentioning
confidence: 99%